Electric Vehicle Charging Station Planning Based on Weighted Voronoi Diagram - Liang Feng; Shaoyun Ge; Hong Liu (2012 Asia-Pacific Power and Energy Engineering Conference, 2012)
This paper presents a novel method for electric vehicle charging station planning based on weighted Voronoi diagram. First, the traffic flow of each intersection node is used to represent the road network traffic. The number of charging stations is estimated in accordance with the capacity of conventional-standard charging station. The initial locations are determined by using coordinate method. Then, weighted Voronoi diagram is used to partition the road network of planning area. The users' minimum loss on the way to the charging station is chosen as the objective function for locating the charging station. Through repeated adjusting the coverage of each partition and the locations of charging stations, its sites and capacities are optimized. The practical example proves that the methods and models in this paper are feasible.